PERANCANGAN DAN ANALISIS VIDEO DOKUMENTER PRODUK EKSPOR TURUNAN KELAPA DENGAN METODE MDLC - Jimmy Pratama; Juliantio Juliantio (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Coconut derivative export products are a collection of original processed products from the coconut plant which are processed through several methods. These products have been processed so that their shape can no longer be recognized by the public. In terms of selling value, these products have promising prices in the international market via export trade. Perhaps we often encounter these products but the origin is unknown, and the level of exports in Indonesia is still relatively minimal. With this research, it is hoped can provide knowledge and stories behind these products in a creative and cinematic manner as well as educate the audience. The method used is a qualitative approach with an MDLC development model conducted by interviewing 6 Indonesian citizens who work as processors of these products. It is hoped that the results can develop public insight, especially among coconut exporters so that exports of these products can increase significantly. This study analyzed the form of a content expert test on 2 coconut derivative product experts and a media expert test on 2 multimedia experts using the Gregory formula. The results of the content expert and media expert test are "1.00" and the audience response test is "92.00%".